Antihyperuricemic Effect of the Combination of Eleutherine bulbosa and Syzygium polyanthum Extracts on Uric Acid Reduction in Hyperuricemic Mice - Indriani, Amanda; Hujjatusnaini, Noor; Nurindahsari, Lilin Ika (Universitas Syiah Kuala, 2025)
Hyperuricemia is a metabolic disorder characterized by elevated serum uric acid levels, which may lead to gout and other related complications. Long-term pharmacological treatments often cause adverse effects, making natural products a promising alternative therapy. This study aimed to evaluate the antihyperuricemic activity of a combined extract of Eleutherine bulbosa (Dayak onion) and Syzygium polyanthum (bay leaf) in hyperuricemic mice (Mus musculus). The experiment employed a post-test only control group design using 28 male Balb/c mice induced with a high-purine diet to establish hyperuricemia. Treatments included single and combined extracts of E. bulbosa and S. polyanthum at doses of 100, 200, and 300 mg/kg body weight with a ratio of 1:2, alongside a positive control (allopurinol). Phytochemical analysis revealed the presence of flavonoids, tannins, and saponins, which act as xanthine oxidase inhibitors and synergistic antioxidants. Statistical analysis using one-way ANOVA indicated a significant effect of the extract combination on reducing serum uric acid levels (p = 0.016). Further Duncans post-hoc test identified the 200 mg/kg dose (1:2 ratio) as the most effective, exhibiting a response comparable to allopurinol. These results suggest that the combination of E. bulbosa and S. polyanthum extracts possesses significant antihyperuricemic potential and may serve as a candidate for the development of stable phytopharmaceutical formulations for hyperuricemia therapy